Individualized Perspective on Spatial Restructuring of E-commerce Villages: A Case Study of Village Q in Shaanxi Province, China - Deng, Liangkai; Wang, De (AESOP, 2024)
The introduction of e-commerce in rural areas is profoundly reshaping the modes of production and lifestyle in these regions, altering the developmental trajectories of villagers, and promoting the restructuring of rural spaces. This study uses Q Village in Shaanxi Province, China,as a case study, employing semi-structured interviews, activity log surveys, and sales data analysis to explore the spatial restructuring of the rural e-commerce landscape from an individual perspective. The findings reveal: (1) E-commerce provides unique developmental pathways for rural individuals, enabling them to transcend traditional kinship and geographic constraints and establish a nationwide economic network, thereby enhancing their economic income; (2) E-commerce expands the sales reach of rural individuals, shifting the traditional geographically-based economic patterns towards regionalization; (3) Ecommerce transforms the traditional organization of production spaces in rural areas, moving from a village-centered to a layout centered around fields, residences, and towns; (4) Under the influence of ecommerce, the living time of rural individuals is compressed by production demands, increasing temporal pressures on individuals. These results offer insights for developing and constructing rural spaces influenced by e-commerce. Keywords: E-commerce Villages, Spatial Restructuring, Individualization, Rural Revitalization
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024